Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1136/jech.2006.057273
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of symptoms of post-traumatic stress disorder after the AZF chemical factory explosion on 21 September 2001, in Toulouse, France

Abstract: Individual vulnerability, exposure and post-trauma factors were associated with S-PTSD. Vulnerable subgroups, defined by low socioeconomic characteristics may warrant focused screening after such disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…The immediate area in our study corresponds overall to a socioeconomic environment that enjoys less advantages than the rest of the city [39]. Occupation of industrial space and adjoining areas by housing that supplies low-qualified workers to surrounding businesses has led to a concentration of underprivileged areas around the chemical complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The immediate area in our study corresponds overall to a socioeconomic environment that enjoys less advantages than the rest of the city [39]. Occupation of industrial space and adjoining areas by housing that supplies low-qualified workers to surrounding businesses has led to a concentration of underprivileged areas around the chemical complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Toulouse, the populations of the immediate area were not only exposed to industrial risk but also in addition they live in an area where economic and collective resources are scarcer than elsewhere. In a study of the same disaster, Rivière et al [39] showed that low socioeconomic status was associated with S-PTSD in the general population in this area. The association between underprivileged areas and chemical industries has already been described: the more underprivileged the areas, the more they tend to concentrate dangerous chemical facilities around their perimeters [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance of the individual from the place of event and levels of exposure are very significant risk factors in occurence of PTSD especially in industrial explosions (5). Presence of psychiatric disorders before the disaster has been reported to be another risk factor.…”
Section: Introductionmentioning
confidence: 99%